2019
DOI: 10.1021/acs.jnatprod.9b00646
|View full text |Cite|
|
Sign up to set email alerts
|

Benzophenone Compounds, from a Marine-Derived Strain of the Fungus Pestalotiopsis neglecta, Inhibit Proliferation of Pancreatic Cancer Cells by Targeting the MEK/ERK Pathway

Abstract: Pancreatic cancer, which has an extremely poor prognosis, is one of the most fatal human cancers. Chemotherapy is the main palliative treatment for advanced cancer patients and also plays an indispensable role in postoperative treatments for surgical patients. Therefore, there is an urgent need to develop more innovative anticancer drugs to fight against this fatal disease.Here, we investigate the potential of benzophenone derivatives, obtained from a marine-derived strain of the fungus Pestalotiopsis neglecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In particular, 266 and 268 were found to suppress cell proliferation and induce apoptosis in the low micromolar range of 7.6 and 7.2 μmol/L, respectively. [ 135 ]
…”
Section: Marine Habitats For Microorganisms Producing Halogenated Com...mentioning
confidence: 99%
“…In particular, 266 and 268 were found to suppress cell proliferation and induce apoptosis in the low micromolar range of 7.6 and 7.2 μmol/L, respectively. [ 135 ]
…”
Section: Marine Habitats For Microorganisms Producing Halogenated Com...mentioning
confidence: 99%
“…Six new alkenylated tetrahydropyran derivatives belonged to polyketides, designated as (12R,13R)-dihydroxylanomycinol (73), (12S,13S)-dihydroxylanomycinol (74), (12R,13S)-dihydroxylanomycinol (75) and (12S,13R)-dihydroxylanomycinol (76), (12S,13R)-N-acetyl-dihydroxylanomycin (77) and (12S,13S)-N-acetyl-dihydroxylanomycin (78), together with one related known compound lanomycinol (79), were isolated from Westerdykella dispersa (the South China Sea). Compounds 73-79 exhibited moderate antifungal activities selectively against agricultural pathogenic fungi Rhizoctorzia solani, Verticillium dahliae, Helminthosporium maydis, Fusarium tricinctum, F. oxysporum, Botryosphaeria dothidea, and Alternaria fragriae [52].…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Isolated compounds suppressed pancreatic cancer cell line PANC-1 proliferation and induced apoptosis. An in silico study suggested that benzophenone derivatives could potentially inhibit MEK activity by binding to the allosteric pocket in MEK [77].…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…Their application extends beyond the common PL techniques of binding-site and biological-interactome mapping, target identification and proteome profiling, and surface conjugation techniques amongst others. They are also found in natural products that have broad-spectrum biological effects such as anticancer, antiviral, antimicrobial, and anti-inflammatory effects [2,[19][20][21][22]. The phototoxicity of this class of bioactive natural products is a probable adverse effect that may limit the widespread utilization of this pharmacophore in drug design [23].…”
Section: Benzophenonesmentioning
confidence: 99%